Dakwah Pada Masyarakat Multikultural - Fikri, Hamdani Khaerul (Mudabbir: Jurnal Manajemen Dakwah, 2023)
Abstract: This article discusses the role of Islam as a missionary religion in encouraging active participation of its followers in missionary activities in Indonesia, a country rich in linguistic, ethnic, racial, and religious diversity. The close correlation between the progress or regression of the Islamic community and missionary activities creates the reality of a multicultural society in Indonesia. With a large and dispersed population across numerous islands, differences in religion, ethnicity, race, and language can have both positive and negative impacts, including the potential for conflict. The article focuses on a multicultural-based approach in the context of missionary activities, identifying the role of multiculturalism in society and highlighting appropriate missionary strategies. The two main questions addressed in this article are, first, what is the meaning of multiculturalism in society? And second, what are the suitable missionary strategies in the context of a multicultural society? Through this discussion, the article provides a profound understanding of the complex dynamics among missionary activities, Islam, and multicultural society in Indonesia. It demonstrates that successful missionary strategies have been implemented in multicultural communities and also offers valuable insights for readers interested in religious and multicultural issues.